Global competence in higher education: a ten-year systematic literature review - Jiaxin, Guo; Huijuan, Zhuang; Md Hasan, Howlader (Frontiers in Education, 2024)
In the current epoch of economic globalization, the globalization of higher education has spurred an increasing interest in comprehending global competence. A systematic literature review was conducted, analyzing a wide range of studies from 2013 to 2023 using the Web of Science and Scopus databases. The review aimed to present an updated overview of research on global competence, covering various aspects such as its definition, assessment dimensions, research objectives, methodologies, results, and limitations. Most publications define global competence using knowledge, attitudes, and skills as crucial dimensions, drawing from international organizational documents and research findings. However, the review also emphasizes the need for future research to adopt a longitudinal approach and develop global competence verification tools to measure global competence among university students and faculty. By providing a comprehensive analysis of current research, this review highlights the importance of understanding global competence in higher education and its potential impact on students and faculty in an increasingly interconnected world.